Effect of sugarcane bagasse biochar on soybean germination and initial growth - Lorrana Zelia Martins de Souza; Halax Duart Martins Silva; Giovanni Uema Alcantara; Bruna Cristina Pinto; Adriana Duneya Diaz Carillo; Osania Emerenciano Ferreira; Gustavo Henrique Gravatim Costa; Alan Machado (The Journal of Engineering and Exact Sciences)
Biochar is known as an excellent soil conditioner and a powerful carbon sequestration tool. However, to expand its use, it is necessary to understand potential adverse effects. To better address this issue, biochar was prepared from sugarcane bagasse. The effect of biochar on the germination of soybean seeds was evaluated, and a greenhouse experiment was conducted to assess the response of soybean seedlings to biochar application at different rates (CK, 0% w/w; BC1, 1% w/w; BC3, 3% w/w; and BC5, 5% w/w). Thirty days after sowing, the growth parameters, soil physicochemical attributes, and microbiota were evaluated. The biochar exhibited a low O/C ratio (0.18) and an irregular porous surface, which promoted improvements in the soil’s physical, chemical, and biological attributes. Moreover, no phytotoxic effects were detected in the germination tests for application rates up to 50 t/ha. The results of soybean cultivation revealed that, compared with the CK treatment, the BC3 and BC5 treatments significantly increased the fresh mass of the aerial parts of the plants by 64% and 86%, respectively. These treatments also significantly increased the fresh mass of the root system by 23% and 423%, respectively. These results highlight the potential of biochar in promoting early soybean development.